Consumer liking of M. longissimus lumborum from New Zealand pasture-finished lamb is influenced by intramuscular fat. (March 2021) - Realini, C.E.; Pavan, E.; Johnson, P.L.; Font-i-Furnols, M.; Jacob, N.; Agnew, M.; Craigie, C.R.; Moon, C.D.
Abstract: Palatability of meat is known to be affected by intramuscular fat (IMF), but the effect in relatively low-fat New Zealand lamb is unknown. This study evaluated the eating quality of 108 loins ( M. longissimus lumborum ) from a single flock of ewe-lambs. Loins ranged from 1.09–5.68% IMF and were stratified into 6 groups: 1.65, 2.12, 2.65, 3.20, 3.58 and 4.40%. Consumers' (n = 165) overall liking of lamb increased significantly at around 3% IMF, achieving maximum scores at 4% IMF. One consumer cluster (n = 111) showed a linear increase in overall liking with increasing IMF%, regarded as 'IMF lovers: the more the better', while a second cluster (n = 54) preferred 2.5–3.5% IMF, described as 'IMF optimizers: just the right amount'. IMF% was modestly correlated ( + 0.25) with all sensory attributes except juiciness. Liking scores were modestly correlated with monounsaturated ( + 0.25) and polyunsaturated ( − 0.20) fatty acids. Results suggest aiming for IMF% levels in New Zealand lamb beyond 3% to maximize eating quality for premium markets in particular. Highlights: Consumer liking increased with increasing intramuscular fat (IMF%) peaking at 4%. Two consumer clusters were identified with different preferences for IMF% in lamb. Intramuscular fat was correlated with all sensory attributes except juiciness. Liking was correlated with monounsaturated (+) and polyunsaturated (−) fatty acids.